Werner Heisenberg and Thomas Aquinas on Natural Indeterminism. (1st October 2013) - Silva, Ignacio
Abstract When Werner Heisenberg presented his views of the fundamental indeterminism to which his uncertainty principle pointed in the basic levels of reality described by quantum mechanics, he used the Aristotelian technical terms of act and potency, affirming that the quantum system is in potency before the measurement and that the potency was actualised when the measurement took place, speaking thus of a 'new ontology' of quantum mechanics. I argue that Thomas Aquinas' Aristotelian account of indeterminism in nature, through his analysis of the notions of matter as potency and form as act, can provide a suitable framework to understand Heisenberg's philosophical intuition about the nature of quantum systems.